1996
DOI: 10.1073/pnas.93.6.2264
|View full text |Cite
|
Sign up to set email alerts
|

Balancing immunity and tolerance: deleting and tuning lymphocyte repertoires.

Abstract: Immunological self-tolerance is ensured by eliminating or inhibiting self-reactive lymphocyte clones, creating physical or functional holes in the B- and T-lymphocyte antigen receptor repertoires. The nature and size of these gaps in our immune defenses must be balanced against the necessity of mounting rapid immune responses to an everchanging array of foreign pathogens. To achieve this balance, only a fraction of particularly hazardous self-reactive clones appears to be physically eliminated from the reperto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
270
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(276 citation statements)
references
References 254 publications
(190 reference statements)
5
270
0
1
Order By: Relevance
“…5,6 It is well established that the strength of antigen receptor signals is a key determinant in tolerance induction, as it dictates the positive and negative selection of B and T cells. 7 As the proteins involved in antigen receptor signalling must operate within complex biochemical pathways, it is plausible that quantitative or qualitative perturbations owing to heterozygosity of multiple genes might have additive or synergistic effects with respect to immune regulation. In keeping with this notion, studies of compound heterozygote mice have revealed the importance of threshold levels of proteins in controlling immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 It is well established that the strength of antigen receptor signals is a key determinant in tolerance induction, as it dictates the positive and negative selection of B and T cells. 7 As the proteins involved in antigen receptor signalling must operate within complex biochemical pathways, it is plausible that quantitative or qualitative perturbations owing to heterozygosity of multiple genes might have additive or synergistic effects with respect to immune regulation. In keeping with this notion, studies of compound heterozygote mice have revealed the importance of threshold levels of proteins in controlling immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…3 Cell apoptosis is one of the mechanisms involved in the control of T-cell homeostasis, 4 causing the deletion of autoreactive T cells. 5 Most T cells in the airways of untreated asthmatic patients are not apoptotic. 6 Moreover, in patients with asthma, peripheral blood T cells (PBTs) are characterized by an increased activation state and by reduced apoptosis.…”
mentioning
confidence: 99%
“…Although BCR expression is critical for B cell differentiation (37,38), engagement of the BCR with self-Ag can profoundly influence the fate of B cell development. The ultimate fate of an autoreactive B cell depends upon several factors, such as the form and location of Ag, Ag concentration, structure, the affinity of the expressed BCR, and the availability of T cell helper activity (34,36). Mice that are made transgenic for both Ig with high Ag-binding affinity and specific Ag, experience either anergy or deletion of B cells that expressed the Ig transgenes, unless they undergo Ig receptor editing to express BCR that no longer react with the transgenic Ag (39).…”
Section: Discussionmentioning
confidence: 99%